Practical review of the place of social networks in our daily life and their effect on today’s youth, - Korkmaz, M., Çelebi, N., Yücel, A. S. (My University, 2014)
In this study, we practically reviewed the negative effects of social networks on today’s youth which became somewhat indispensable to them. The study was based on the university students attending public and private universities and the high-school students. The number of participants included in the study is 894 individuals in total. The study was completed in an eight month period. Within this period, specific student groups were asked to fill in a survey composed of eighty questions on their own free will and choices. While the survey had two sections, the 60 questions in the first section were prepared in a 5-point Likert scale. In the first section, questions towards the use of social networks were answered. The last 20 questions were demographic which were arranged as multiple-choice questions. The data from the survey were analyzed via the statistical program SPSS 15. The results of the analysis and findings were presented as tables and explanations at the end of the study. This study contributes to the understanding of social status and problems experienced by today’s youth related to the social networking web pages. At the end of the research, we came to the conclusion that social networks had a negative effect on the youth.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Internet; Youth; Education; University; Student; Social Networks